2014
DOI: 10.1590/1808-1657001792011
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de inseticidas a alguns dos inimigos naturais na cultura do algodão

Abstract: O objetivo foi estudar a seletividade de inseticidas aos inimigos naturais na cultura do algodão (Gossypium hirsutum L.r. latifolium Hurtch), cultivar DeltaOpal, no município de Malhada (BA) e conhecer a fauna benéfica associada. O trabalho foi conduzido na safra 2010/2011, com delineamento experimental em blocos ao acaso, com seis tratamentos e quatro repetições, sendo os tratamentos: (1) Fipronil 200 SC (0,38 L.ha-1); (2) Alfacipermetrina 100 SC (0,30 L.ha-1); (3) Lufenuron 50 CE (0,30 L.ha-1); (4) Imidaclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Insecticides also negatively affect the survival of beneficial arthropods. Diamantino et al (2014) evaluated the selectivity of synthetic products on parasitoids in the cotton plant cultivar DeltaOpal in the southwest of Bahia State, Brazil. The authors found that mortality caused by a variety of products (Fipronil ® 200 SC, Alfacipermetrina 100 SC, Lufenuron ® 50 EC, Imidacloprid ® 200 SC, and Parathion methyl ® 600 EC) was accentuated in different applications of pesticide.…”
Section: Introductionmentioning
confidence: 99%
“…Insecticides also negatively affect the survival of beneficial arthropods. Diamantino et al (2014) evaluated the selectivity of synthetic products on parasitoids in the cotton plant cultivar DeltaOpal in the southwest of Bahia State, Brazil. The authors found that mortality caused by a variety of products (Fipronil ® 200 SC, Alfacipermetrina 100 SC, Lufenuron ® 50 EC, Imidacloprid ® 200 SC, and Parathion methyl ® 600 EC) was accentuated in different applications of pesticide.…”
Section: Introductionmentioning
confidence: 99%
“…Insecticide selectivity to natural enemies has been studied for decades (HASSAN et al, 1998;ZOTTI et al, 2008;FONSECA et al, 2012;DIAMANTINO et al, 2014). However, in addition to being specific to the biological organism under study and its phases of development, pesticide selectivity is directly related to its concentration (DESNEUX et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…O uso indiscriminado de inseticidas químicos pode contribuir para o aumento da presença e de ataque da praga à cultura. Entre as consequências mais comuns do uso incorreto dos agrotóxicos, pode-se citar resistência do inseto-praga ao inseticida, tornando sua ocorrência mais frequente, e a redução na população de inimigos naturais, principalmente, pelo uso de inseticidas não seletivos (DIAMANTINO et al, 2014;SPARKS e NAUEN, 2015).…”
unclassified